How Do Parental Acceptance–Rejection, Power, and Prestige Affect Psychological Adjustment? A Quantitative Study With a Sample of Portuguese College Students. (August 2014) - Machado, Márcia; Machado, Francisco; Neves, Sofia; Fávero, Marisalva
This article discusses the relationship between perceived paternal and maternal acceptance, parental power and prestige, and psychological adjustment, having in mind national and international gender equality indicators. The sample consisted of 785 Portuguese college students, 44% of whom were men. The participants ranged in age from 18 through 62 years ( M = 22.38). Measures used were Portuguese translations of the adult versions of the Parental Acceptance–Rejection Questionnaire for mothers and fathers, and the Personality Assessment Questionnaire, as well as the Parental Power–Prestige Questionnaire. Gender differences were found only in perceived parental power, with men perceiving fathers as being more powerful than did women. The study concluded that parental power (especially paternal power) moderated the relation between perceived paternal acceptance and women's psychological adjustment. However, parental prestige (especially paternal prestige) moderated the relation between perceived paternal acceptance and men's psychological adjustment.